Konsep Etika Religius Ibnu Athā’illah Al-Sakandarī - Bayu Fermadi (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2019)
Abstract: Ethics is a social action that continues to affect, reflect all human actions in general, whether the actions are good or bad. Universal, ethics can be interpreted as a form of custom, custom, morals, character, feelings and attitude. the concept of ethics in general can not be separated from the base that affects the formation of ethics is the religion of Islam (Islam islamic) which became the main source of ethical review process - religious reading - in the reality of everyday life. In Islam's view the construction of the above ethics is built through several processes, theological, theological, the morality, the scriptural, the philosophical ethics. The striking difference that religious ethics holds is primarily rooted in the Qur'an and as-Hadith, which significantly tends to divest the dialectics and focus on attempts to expel the spirit of Islamic morality in a more specific way to the study of religious ethics of Ibnu Athā ' god trying to get out of the craze of developing thoughts and passively choosing social problems. So came the concept of religious ethics that are universal like sincere, patient, honest and trustworthy. Keywords: Religious Ethics, Ibnu Athā'illah Al-Sakandarī